A standardized protocol to reliably visualize the left atrial appendage with intracardiac echocardiography: Importance of multiple imaging sites. Issue 10 (25th July 2018) - Basman, Craig; Alderwish, Edris; Rambhatla, Tarak; Vaishnav, Aditi; Kronzon, Itzhak; Mountantonakis, Stavros E.
Abstract : Background: Currently, there is no accepted protocol for left atrial appendage (LAA) imaging with intracardiac echocardiography (ICE). Objective: This study aimed to assess the utility of ICE to reliably visualize the entire cavity of the LAA and propose a specific procedural protocol to achieve the above objective. Methods: We created a three‐dimensional reconstruction of the LAA, using two‐dimensional ICE sections obtained from three different location (the right atrium [RA], right ventricle inflow [RVI], and right ventricular outflow [RVOT]). We then compared the three‐dimensional LAA reconstruction by ICE with one obtained by cardiac computed tomography angiography (CCTA) for morphological and volume differences. Results: Three‐dimensional reconstruction with ICE could reliably reproduce the LAA as visualized with CCTA but only when ICE sampling was performed from at least two catheter positions. There was no statistically significant difference between LAA volumes obtained with ICE and CCTA ( P = 0.33). The contribution of each anatomical location to the total volume was 17% ± 16.6%, 74% ± 13.3%, and 33% ± 26% for RA, RVI, and RVOT, respectively. Conclusion: In comparison with CCTA, the LAA can be reliably visualized in its entity by ICE, but only if multiple imaging positions (RA, RV inflow, and RVOT) are used.